Crohn's disease - Allman, Toney (Diseases and disorders, 2012)
"This series objectively and thoughtfully explores topics of medical importance. Books include sections on a description of the disease or disorder and how it affects the body, as well as diagnosis and treatment of the condition"-- Provided by publisher